The effect of leader trust and knowledge sharing on staff satisfaction at work: investigation of universities in Syria - Dalati, Serene; Alchach, Hala (Business, Management and Economics Engineering, 2018)
This research paper examines the effect of leader trust, organisational trust and knowledge sharing on staff attitudes and satisfaction at work at universities in Syria. The research methodology employs a quantitative design of questionnaire instrument. The model predicts that if employees develop high levels of trust in their leader and organizations, this will stimulate a good quality relationship and develop satisfaction at work. Leader trust, Knowledge sharing behaviour and job satisfaction subscales are based on prior research measures. Sampling strategy employed non-probability sampling. The size of the sample is 161. The results of the research designate that trust in leader and knowledge sharing behaviours are positively associated with employee job satisfaction.